Excel 2016 Power Programming with VBA. - Alexander, Michael, 1972-; Kusleika, Dick (Mr. Spreadsheet's bookshelf., 2016)
Encompassing an analysis of Excel application development and a complete introduction to Visual Basic for Applications (VBA) - with over 800 pages of tips, tricks, and best practices, this comprehensive book presents all of the techniques you need to develop both large and small Excel applications. --